2020
DOI: 10.1080/13229400.2020.1835694
|View full text |Cite
|
Sign up to set email alerts
|

Meeting online and family-related outcomes: evidence from three German cohorts

Abstract: In recent years, the Internet has become an increasingly important venue for meeting partners. While meeting online may have a range of effects on family-related outcomes, studies on the link between meeting online and family-related outcomes are scarce. Using eight follow-up waves of the German Family Panel (Pairfam), with observations from 8177 persons from three birth cohorts between 2009 and 2016, this study investigates whether meeting online is associated with relationship satisfaction, intention to sepa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This technology is cost-effective, fast, user-friendly ( Wiederhold, 2015 ), and has the potential to facilitate the formation of both short-term and long-term relationships ( Danielsbacka, Tanskanen, & Billari, 2022 ), thereby mitigating feelings of loneliness ( Sumter, Vandenbosch, & Ligtenberg, 2017 ). However, in addition to these positive effects, research has identified associations between the compulsive use of dating apps and offline interpersonal problems ( Sharabi & Timmermans, 2021 ), as well as higher levels of psychological distress, and symptoms of anxiety and depression ( Holtzhausen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technology is cost-effective, fast, user-friendly ( Wiederhold, 2015 ), and has the potential to facilitate the formation of both short-term and long-term relationships ( Danielsbacka, Tanskanen, & Billari, 2022 ), thereby mitigating feelings of loneliness ( Sumter, Vandenbosch, & Ligtenberg, 2017 ). However, in addition to these positive effects, research has identified associations between the compulsive use of dating apps and offline interpersonal problems ( Sharabi & Timmermans, 2021 ), as well as higher levels of psychological distress, and symptoms of anxiety and depression ( Holtzhausen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%